THE INFLUENCE OF GREEN ZONE OFFICES TO THE GOVERNMENT ECOMONY - Sobirova Elgiza Alibek kizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
This  article  explains  how  government  economies  are  affected  by  green  zone offices,  emphasizing  how  these  offices  may  advance  sustainable  practices,  draw  in investment, and improve public health. Green zones encourage the public and business communities  to  support  sustainable  projects  by  acting  as  role  models  for environmentally friendly infrastructure. These zones can boost regional economies and encourage the development of jobs by establishing appealing settings for investment. The nature can easily influence to a working mood and feeling power of environment but  not  pressure  of  office  is  a  brilliant  atmospherefor  people  who  is  in  any  ages  . Furthermore, green areas raise property prices, lower healthcare expenses, and enhance public health, all of which benefit local governments' tax collections. The essay focuses on how green zones improve community involvement while simultaneously elevating governments to the status of world leaders in sustainability and influencing foreign policy. In the end, governments have a great chance to promote economic development and solve serious environmental issues by creating green zone offices.